Dairy farm management: a typology of dairy farmers according to their disposition to the use of economic and physical records - Piñeiro, D.; Chiappe, M.; Graña, F. (Agrociencia Uruguay, 2022)
The technological model applied during the last years in Uruguayan dairy production has made it possible to consolidate the efficiency and productivity of dairy farmers. Although for many dairy producers there is still room to incorporate new production techniques, the most advanced producers seem to have reached their ceiling in the possibilities of improving the recommended technological package for dairy production. In consequence, for these farmers, keeping economic records is becoming increasingly important at the planning and decision-making stages. In this study, we describe in the first place the different behaviors of dairy producers from the perspective of the management of their farms, and we identify the variables that are underlying these diverse behaviors. In the second place, we construct a typology of dairy farmers, distinguishing four categories: (1) Disintegrating farmers, (2) Agribusiness wage-laborers, (3) Quasi-entrepreneurs, and (4) Diversified entrepreneurs. Finally, the study concludes with some thoughts regarding the feasibility of using physical, economic and financial records for each of the identified types of dairy farmers.